2007
DOI: 10.1111/j.1600-0714.2007.00608.x
|View full text |Cite
|
Sign up to set email alerts
|

Combinational polymorphisms of four DNA repair genes XRCC1, XRCC2, XRCC3, and XRCC4 and their association with oral cancer in Taiwan

Abstract: We have identified the potential combined XRCCs 1-4 SNPs with genotypes that were associated with oral cancer risk and may have an impact on identification of a high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
56
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(65 citation statements)
references
References 38 publications
(75 reference statements)
7
56
2
Order By: Relevance
“…TaqMan real-time PCR, for instance, has been applied to SNP genotyping in many association studies [3,8,9] but some SNPs cannot be genotyped using TaqMan probes [10-12]. As an alternative, PCR-restriction fragment length polymorphism (RFLP) analysis is able to provide cost-effective SNP genotyping and mutation detection [12-14]. However, RFLP mining for SNPs in a genome is a complex task when manually performed.…”
Section: Introductionmentioning
confidence: 99%
“…TaqMan real-time PCR, for instance, has been applied to SNP genotyping in many association studies [3,8,9] but some SNPs cannot be genotyped using TaqMan probes [10-12]. As an alternative, PCR-restriction fragment length polymorphism (RFLP) analysis is able to provide cost-effective SNP genotyping and mutation detection [12-14]. However, RFLP mining for SNPs in a genome is a complex task when manually performed.…”
Section: Introductionmentioning
confidence: 99%
“…XRCC1 polymorphisms were first reported as a risk factor for oral cancer (Sturgis et al 1999). Since then, a number of studies have confirmed or refuted this phenomenon (Majumder et al 2005(Majumder et al , 2007Matullo et al 2006;Ramachandran et al 2006;Kietthubthew et al 2006;Ho et al 2007;Yen et al 2008). These disparate findings may be due to insufficient power in some studies, differences between cancer types, type of study populations and study design.…”
mentioning
confidence: 99%
“…This change may influence their protein activity, resulting in differences of individual DNA repair capacity (DRC) that may affect the susceptibility of oral cancer. Growing number of studies have been done to examine the relationship between this SNP and the risks of oral cancer (Benhamou et al, 2004;Majumder et al, 2005;Matullo et al, 2006;Kietthubthew et al, 2006;Yang et al, 2008;Yen et al, 2008;Dos Reis et al, 2013). However, the results are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…XRCC3 gene is involved in the repair of DNA double-strand breaks (DSB), which is important to prevent chromosomal fragmentation, translocations and deletions (Kanaar et al, 1998). To date, there are studies reporting the association between polymorphisms of XRCC3 codon 241 with oral cancer risk but these published data were contradictory (Benhamou et al, 2004;Majumder et al, 2005;Matullo et al, 2006;Kietthubthew et al, 2006;Yang et al, 2008;Yen et al, 2008;Dos Reis et al, 2013). Until now, there was no meta-analysis or systematic review on the risk of oral cancer with XRCC3 polymorphism.…”
Section: Introductionmentioning
confidence: 99%